Rational Manipulation of IrO2 Lattice Strain on α‑MnO2 Nanorods as a Highly Efficient Water-Splitting Catalyst - Sun, Wei; Zhou, Zhenhua; Zaman, Waqas Qamar; Cao, Li-mei; Yang, Ji (ACS applied materials & interfaces, 2017)
Developing more efficient and stable oxygen evolution reaction (OER) catalysts is critical for future energy conversion and storage technologies. We demonstrate that inducing a lattice strain in IrO2 crystal structure due to interface lattice mismatch enables an enhancement of the OER catalytic activity. The lattice strain is obtained by the direct growth of IrO2 nanoparticles on a specially exposed surface of α-MnO2 nanorods via a simple two-step hydrothermal synthesis. Interestingly, the prepared hydride OER activity increases with a lower IrO2 grown mass, which offers an opportunity to reduce the usage of precious iridium and ultimately obtains a specific mass activity of 3.7 times than that of IrO2 prepared under the same conditions and exhibits equivalent stability. The lattice mismatch in the underlying interface induces the formation of lattice strain in IrO2 rather than the charge transfer between the materials. The lattice strain changes are in good agreement with the order of the OER activity. Our experimental results indicate that using the special exposed surface substrates or tuning the supporting morphology structure can manipulate the catalyst materials lattice strain for the design of more efficient OER catalysts.